Banking 4.0 - Wo die Reise hingeht - Jessica Hastenteufel; Uli Hagmann (IUBH Internationale Hochschule, 2020)
– The cross-industry megatrend of digitization is changing the understanding of banking. Innovative technologies such as Big Data Analytics, Artificial Intelligence or Cloud Computing are penetrating the financial industry at a rapid pace and are forcing traditional banks to adapt. Modern financial services provided by so-called fintechs or bigtechs are particularly convincing due to their high degree of user-friendliness and ensure increased competi-tive intensity in the financial industry. The retail banking resulting from this digital transformation is called bank-ing 4.0 and will be considered in this paper. The practical effects for customers as well as the challenges for the classical business model of banks are explained by means of selected examples. It turns out that completely digitalized applications unfold their greatest potential through so-called open banking and can thus make the best possible use of the network effects of cooperations. Such platforms are able to provide the appropriate fi-nancial solution individually at any time and any place. This is referred to as embedded banking. which end cus-tomers often experience through so-called smart assistants, which are now installed as standard The associated payment transactions are also becoming increasingly digital, although there are still major regional differences. Decentralized systems such as blockchain technology are used for particularly transaction-intensive applications and already enable cross-border transfers in real time. There is still a large difference between the technically possible and the actually applied banking, but the financial system is also being transformed and redesigned by digitization.
Keywords: G21; O33; 650; Banking 4.0; Digitalisierung